Development and Validation of a new Multidimensional Questionnaire called Muslim Medical Student Questionnaire (MMSQ) among Malaysian Undergraduates - Musa, Ramli; Abdul Rani, M. Fauzi; Che A., Aminudin; Draman, Samsul (IIUM Medical Journal Malaysia, 2018)
Introduction: A handful of medical schools have implemented the Islamic input in medical program into their medical curricula. However we are facing a setback as there is no validated standard assessment tool to measure the effectiveness of this academic input for undergraduate medical programme. Therefore the objective of this study is to design a scale that is able to gauge the impact of the Islamic input among medical undergraduates. Materials and Methods: The construction of a new scale is based on the 5 stages of standard questionnaire design. To validate the newly designed scale, it was administered to all the medical students who granted their consent. Results: A total of 520 students from all academic years of a medical school were enrolled in the validation stage. Bartlet’s KMO value is 0.9. From 46 items, 67% had good factor loading (>0.4). Cronbach’s alpha values of 0.78, 0.85 and 0.13 were obtained for Attitude, Practice and Knowledge domains respectively. We identified the 3 domains by using exploratory factor analysis. Conclusion: The scale has good psychometric values for both reliability and validity.